PENGARUH OWNERSHIP STRUCTURE DAN VOLUNTARY DISCLOSURE IN CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN TAHUN 2011-2016) - Lydia Natalia Funome; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the direct and significant influence of ownership structure and voluntary disclosure in corporate governance to financial distress. The samples used in this research were 39 mining companies listed in Indonesia Stock Exchange starting from 2011-2016. The data processed used WarpPLS software version 5.0.The result of the research found the negative affect of ownership structure on financial distress, the posotive affect of ownership structure on voluntary disclosure in corporate governance, the negative affect of voluntary disclosure in corporate governance on financial distress and the voluntary disclosure in corporate governance failed to mediate the influence of the ownership structure on financial distress.